In silico investigation of HCV and RNA synthesis inhibitor antibiotic drugs as potential inhibitors of SARS‑CoV‑2 main protease (Mpro) - Merusomayajula V. Kishore; T. Siva Rao; G. N. D. Kumari (SpringerOpen, 2024)
Abstract Background Since December 2019, a global crisis has unfolded with the emergence of a new strain of coronavirus known as SARS-CoV-2. This pandemic has afflicted hundreds of millions of people worldwide, resulting in millions of fatalities. In response to this urgent healthcare crisis, extensive efforts have been made to discover inhibitors of the COVID-19 virus. Given the structural similarities between SARS-CoV-2 and HCV, drugs approved by the FDA for treating HCV were selected and subjected to in silico testing against the SARS-CoV-2 virus, with Remdesivir used as the standard for validation. Drug repurposing and phytochemical testing have also been conducted to identify potential candidates capable of inhibiting or suppressing the infection caused by the coronavirus. The time constraints imposed by the pandemic necessitated the in silico analysis of existing drug molecules against the coronavirus. Eleven HCV drugs approved by the FDA, along with one RNA synthesis inhibitor antibiotic drug, were tested using the in silico method due to their structural similarities with HCV and the SARS-CoV-2 virus. Results Molecular docking and MD simulation studies were performed for all selected compounds. Binding energies, root-mean-square deviation, root-mean-square fluctuation, solvent-accessible surface area, radius of gyration, and molecular mechanics generalized born surface area were calculated. Based on docking and MD simulation studies all the selected compounds have shown good binding energy values with Mpro (PDB ID: 6LU7). No toxicity measurements are required for these drugs since they were previously tested prior to their approval by the FDA. Conclusions This study shows that FDA-approved HCV drugs can be used as for SARS-COVID-19 inhibitors.